Design and implementation of a multihoming-based scheme to support mobility management in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hasan, Mohammad Kamrul (Springer Netherlands, 2017)
With the worldwide deployment of different wireless access technologies and expanding requests for worldwide Internet accessibility, Network Mobility (NEMO) is turning out to be all the more requesting innovation. Therefore, NEMO Basic Support Protocol (NEMO BSP) has been anticipated by the NEMO Working Group for the continual worldwide connectivity of each node within the mobile network. Yet, NEMO BSP experiences from higher handoff delay and packet loss. Thus, fails to provide seamless handoff. This issue can be resolved by introducing multihoming concept in NEMO. The reason is to support concurrent use of multiple interfaces on a single Mobile Router. Therefore, the main objective of this paper is to propose an innovative Multihoming-based scheme to support Mobility management in Proxy NEMO (MM-PNEMO) environment. In addition, the performance is assessed utilizing simulation approach to certifying the applicability as well as the efficacy of the suggested scheme. The performance metrics used for evaluation are namely handoff delay, packet loss, packet delivery ratio, as well as throughput. The simulation is done using NS-3 network simulator. The simulation outcomes demonstrate that the proposed MM-PNEMO scheme outperforms the standard NEMO BSP and PNEMO in terms of packet loss (less than 1%) and handoff delay (average improvement by 76%).